KEMAMPUAN MENULIS KARANGAN ARGUMENTASI SISWA KELAS X SMAN 1 PASAMAN DENGAN TEKNIK PEMODELAN - Sari, Linda Oktavia; Krisna, Eva; Helda, Trisna (Pendidikan Bahasa Indonesia, 2014)
This examination is bacground by three problems. First, students capable less to write argumentative opus, second, students donât have ability to pourÂ idea in form argumentative opus, tird use methode not interesting, this examination have gaal to description the ability to write argumentative opus students class x senior high school Negeri 1 Pasaman with use modeling technic, kind of examination is kuantitative examination with descriptive methode, population of this examination students x class SMA Negeri 1 Pasaman have 245 students, the sample of examination have 37 people, from produce examination can know that ability to write argumentative opus students class x SMA Negeri 1 Pasaman with modeling technic are, first to indicator 1 (make the reader is believe) to get mean 98,22, perfect gualification, second indicator II (prave the truth one statetment) to get mean 93,86 with good gualification, third indicator III (change the reader opinion) mean 88,46 with better, generaly the ability to write argumentative opus students class X SMA Negeri 1 Pasaman with modeling technic qualificationis very good has mean governance student 93,24.